2010
DOI: 10.1007/s10439-010-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Bulk Flow in Image-Based Hemodynamic Models of the Carotid Bifurcation: The Influence of Outflow Conditions as Test Case

Abstract: Although flow-driven mechanisms associated with vascular physiopathology also deal with four-dimensional phenomena such as species transport, the majority of the research on the subject focuses primarily on wall shear stress as indicator of disturbed flow. Indeed, the role that bulk flow plays in vascular physiopathology has not been thoroughly investigated, partly because of a lack of descriptors that would be able to reduce the intricacy of arterial hemodynamics. Here, an approach is proposed to investigate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 59 publications
(104 reference statements)
4
44
1
Order By: Relevance
“…3 On the other hand, hemodynamic indicator such as helical flow index was proposed to reveal the global organization of blood flow, which was calculated from a Lagrangian-based method for helical flow quantification based on the velocity data from either computational fluid dynamics or phase contrast magnetic resonance imaging. 33,34,68,69,71,72 Through simulating the blood flow in an idealized model of aortocoronary bypass, Morbiducci et al found a linear inverse relationship between the oscillating shear index (a well-known risk index for atherogenesis) and the HFI. 51,71 Furthermore, based on hemodynamic simulations data of 50 carotid bifurcations, Gallo et al 33 demonstrated that the exposure of each carotid bifurcation to disturbed flow measured by time-averaged wall shear stress, oscillatory shear index and relative residence time decreased as the timeaveraged value of the absolute value of helicity increased.…”
Section: Clinical Diagnosis Of Artery Statusmentioning
confidence: 98%
See 1 more Smart Citation
“…3 On the other hand, hemodynamic indicator such as helical flow index was proposed to reveal the global organization of blood flow, which was calculated from a Lagrangian-based method for helical flow quantification based on the velocity data from either computational fluid dynamics or phase contrast magnetic resonance imaging. 33,34,68,69,71,72 Through simulating the blood flow in an idealized model of aortocoronary bypass, Morbiducci et al found a linear inverse relationship between the oscillating shear index (a well-known risk index for atherogenesis) and the HFI. 51,71 Furthermore, based on hemodynamic simulations data of 50 carotid bifurcations, Gallo et al 33 demonstrated that the exposure of each carotid bifurcation to disturbed flow measured by time-averaged wall shear stress, oscillatory shear index and relative residence time decreased as the timeaveraged value of the absolute value of helicity increased.…”
Section: Clinical Diagnosis Of Artery Statusmentioning
confidence: 98%
“…Morbiducci et al numerically demonstrated that HFI in the carotid arteries maintained the same trend during the cardiac cycle (approximately from 0.2 to 0.3), even in the presence of a different redistribution of the flow rate between the internal and external carotid arteries. 69 In terms of velocity data from PC-MRI, Morbiducci et al 73 firstly proved the possibility of quantifying helical flow in vivo based on the HFI of human aorta. Subsequently, they revealed that the HFI of the human aorta was statistically significant at different phases of systole for a subject, gradually increasing from about 0.35-0.5 and the trend of HFI during the systole was similar for healthy subjects, which further confirmed the strength of the HFI as a method for characterizing and ranking the helical flow.…”
Section: Clinical Diagnosis Of Artery Statusmentioning
confidence: 99%
“…42 In detail, several investigations highlighted the role played by helical blood flow patterns, demonstrating that helical flow is involved not only in flow stability, 6,27,28,31 but also in regulating the processes of mixing and transport at the luminal surface of blood formers involved in the onset and development of the disease. 7,19,20,29,41 Additionally, it was demonstrated that a high amount of helicity in the carotid bifurcation is instrumental in suppressing flow disturbances, flow stagnation and separation, leading to a relative uniformity of WSS in the bifurcation region. 10 In parallel, insights into blood flow topology allowed the definition of geometric variables of carotid bifurcation geometries that mostly affect the underlying hemodynamics.…”
Section: Introductionmentioning
confidence: 98%
“…At this site, the analysis of disturbed shear distribution at the luminal surface (historically driven by histological studies) has been recently complemented by a characterization of intravascular fluid structures. 2,10,29,30 The interest for a more in-depth analysis of intravascular hemodynamics moved from the presumption that the presence of peculiar intravascular flow patterns could elicit atheroprotective fluid-wall interaction processes, thus avoiding the onset of atherogenesis by limiting flow instabilities within the vascular bed. 42 In detail, several investigations highlighted the role played by helical blood flow patterns, demonstrating that helical flow is involved not only in flow stability, 6,27,28,31 but also in regulating the processes of mixing and transport at the luminal surface of blood formers involved in the onset and development of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…18,[24][25][26] Usually, 3D simulations produce such large quantities of data that they are unlikely to be of clinical use unless methods are available to simplify our understanding of the flow dynamics. For example, methods have been developed to identify and quantify bulk-flow features using helicity-based descriptors [27][28][29][30] and coherent structures. 25,[31][32][33] The aim of this work is to investigate the effect of vascular curvature and torsion on flow patterns and wall stresses in the idealised vessels shown in Fig.…”
Section: Introductionmentioning
confidence: 99%